2021
DOI: 10.1094/mpmi-12-20-0347-r
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Deacetylases Are Required for Epichloë festucae Endophytic Cell Wall Remodeling During Establishment of a Mutualistic Symbiotic Interaction with Lolium perenne

Abstract: Epichloë festucae forms a mutualistic symbiotic association with Lolium perenne. This biotrophic fungus systemically colonizes the intercellular spaces of aerial tissues to form an endophytic hyphal network, and also grows as an epiphyte. However, little is known about the cell wall remodelling mechanisms required to avoid host defence and maintain intercalary growth within the host. Here we use a suite of molecular probes to show that the E. festucae cell wall is remodelled by conversion of chitin to chitosan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…More research is also required to better understand to what extent secreted GH proteins of plant-associated fungi and oomycetes interact synergistically with each other or other CAZymes to perform their roles, as has been shown for FgXyr1 (GH10) and FgPg1 (GH28) of F. graminearum , which function synergistically to promote virulence in soybean and wheat ( Paccanaro et al, 2017 ). Indeed, several other CAZymes have now been shown to be important virulence factors of plant-associated fungi and oomycetes, including CEs ( Gui et al, 2018 ) chitin deacetylases ( Cord-Landwehr et al, 2016 ; Gao et al, 2019 ; Noorifar et al, 2021 ; Rizzi et al, 2021 ), PLs ( Fu et al, 2015 ; Yang et al, 2018 ), and lytic polysaccharide monooxygenases (LPMOs; Sabbadin et al, 2021 ). Another class of proteins not yet classified as CAZymes, but that have a DUF3129 domain (called effectors with chitinase activity; EWCA), have also been recently implicated in fungal virulence ( Martínez-Cruz et al, 2021 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…More research is also required to better understand to what extent secreted GH proteins of plant-associated fungi and oomycetes interact synergistically with each other or other CAZymes to perform their roles, as has been shown for FgXyr1 (GH10) and FgPg1 (GH28) of F. graminearum , which function synergistically to promote virulence in soybean and wheat ( Paccanaro et al, 2017 ). Indeed, several other CAZymes have now been shown to be important virulence factors of plant-associated fungi and oomycetes, including CEs ( Gui et al, 2018 ) chitin deacetylases ( Cord-Landwehr et al, 2016 ; Gao et al, 2019 ; Noorifar et al, 2021 ; Rizzi et al, 2021 ), PLs ( Fu et al, 2015 ; Yang et al, 2018 ), and lytic polysaccharide monooxygenases (LPMOs; Sabbadin et al, 2021 ). Another class of proteins not yet classified as CAZymes, but that have a DUF3129 domain (called effectors with chitinase activity; EWCA), have also been recently implicated in fungal virulence ( Martínez-Cruz et al, 2021 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Research on fungi, in particular, has shown that the cell wall is dynamic, with ongoing remodeling required for the morphological differentiation of specialized infection structures in planta . Such remodeling is necessary to protect fungal cell wall carbohydrates against hydrolysis by plant-derived enzymes, as well as to prevent their detection by PRRs ( El Gueddari et al, 2002 ; Fujikawa et al, 2009 , 2012 ; Oliveira-Garcia and Deising, 2013 , 2016 ; Becker et al, 2016 ; Noorifar et al, 2021 ). As might be expected, however, this remodelling also runs the risk of releasing MAMPs (e.g., chitin and β-glucan fragments) that activate the plant immune system ( Miya et al, 2007 ; Shimizu et al, 2010 ; Cao et al, 2014 ; Sánchez-Vallet et al, 2015 ; Fesel and Zuccaro, 2016 ; Rovenich et al, 2016 ; Wanke et al, 2020 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…And how do they do it? Why do chitin deacetylases typically occur in multigene families [ 24 , 25 ]? What is the DP, F A , and PA of these natural chitosans?…”
Section: Why Studying Fungal Chitosans?mentioning
confidence: 99%
“…Another possibility could be that V. inaequalis deacetylates chitin to chitosan during host colonization to avoid activation of plant defences, as reported for other plant-associated fungal pathogens (33, 35, 80, 81) and endophytes (34). In line with this, we observed that runner hyphae and stromata developed in culture and in planta were completely covered with chitosan.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, as the apoplast is rich in plant-derived glucanases and chitinases (29), fungi must also actively prevent the hydrolytic release of chitin and β-glucan oligomers from their cell walls (31). One proposed strategy used by fungi is to deacetylate chitin to chitosan (32)(33)(34)(35), which is a poor elicitor of plant defences (36)(37)(38) and a weak substrate of plant chitinases (39,40). Another strategy is to accumulate α-1,3-glucan on the cell surface, which shields it from the action of plant hydrolases and, in doing so, prevents the release of carbohydrate-based MAMPs (41)(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%